Exploring the antimicrobial and antioxidant properties of Lentzea flaviverrucosa strain E25-2 isolated from Moroccan forest soil - Rammali, Said; Ciobică, Alin; El Aalaoui, Mohamed; Rahim, Abdellatif; Kamal, Fatima Zahra; Dari, Khadija; Khattabi, Abdelkrim; Romila, Laura; Novac, Bogdan; Petroaie, Antoneta; Bencharki, Bouchaib (Frontiers in Microbiology, 2024)
The alarming rise in antimicrobial resistance (AMR) has created a significant public health challenge, necessitating the discovery of new therapeutic agents to combat infectious diseases and oxidative stress-related disorders. The Lentzea flaviverrucosa strain E25-2, isolated from Moroccan forest soil, represents a potential avenue for such research. This study aimed to identify the isolate E25-2, obtained from soil in a cold Moroccan ecosystem, and further investigate its antimicrobial and antioxidant activities. Phylogenetic analysis based on 16S rRNA gene sequences revealed the strain’s classification within the Lentzea genus, with a sequence closely resembling that of Lentzea flaviverrucosa AS4.0578 (96.10% similarity). Antimicrobial activity in solid media showed moderate to strong activity against Staphylococcus aureus ATCC 25923, Bacillus cereus strain ATCC 14579, Escherichia coli strain ATCC 25922, Candida albicans strain ATCC 60193 and 4 phytopathogenic fungi. In addition, ethyl acetate extract of this isolate demonstrated potent antimicrobial activity against 7 clinically multi-drug resistant bacteria. Furthermore, it demonstrated antioxidant activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radicals, as well as a significant increase in ferric reducing antioxidant power. A significant positive correlation was observed between antioxidant activities and total content of phenolic compounds (p < 0.0001), along with flavonoids (p < 0.0001). Furthermore, gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of amines, hydroxyl groups, pyridopyrazinone rings, esters and pyrrolopyrazines. The Lentzea genus could offer promising prospects in the fight against antibiotic resistance and in the prevention against oxidative stress related diseases.